Automatic mapping of concrete strength in structural element - Hamid, Roszilah; Mohamed, Ramizi; Mohd. Nayan, Khairul Anuar; Osman, Siti Aminah; Mohd. Yusof, Kamarudin (2006)

(untitled)
Collapses of structure under construction can be prevented if quality control is practiced at sites. The strength uniformity of reinforced concrete structure element cast on site depends on the level of compaction of the fresh concrete. The whole element should be checked and mapped so that localized defect can be detected and removal of formwork can be stopped if applicable. A portable and quick way to check and map the uniformity and the strength of concrete has been developed utilizing the use of pressure wave and signal processing techniques. An echo is introduced to the sample by dropping a small steel ball from a certain height from the concrete surface. The impact generates stress wave, which propagate through the concrete. The accelerometer receives the wave and changes the display from time to frequency domain. The highest observed frequency is determined as the depth frequency. The velocity is calculated as CP = 2fD. Hundreds of specimens were tested. The relationship between the strength and the velocity is correlated. From correlation equation, the strength of concrete can be estimated within 10% error (Hamid et al, 2004). The mapping process is done automatically in computer-generated program. Signal-processing techniques were used to compute the data; Fourier Transform to translate a time-series signal into frequency domain, concrete strength calculation, interpolation technique and a Graphic User Interface (GUI) to complete the mapping algorithms.